2021
DOI: 10.1038/s41467-021-22792-y
|View full text |Cite
|
Sign up to set email alerts
|

Size, microhabitat, and loss of larval feeding drive cranial diversification in frogs

Abstract: Habitat is one of the most important factors shaping organismal morphology, but it may vary across life history stages. Ontogenetic shifts in ecology may introduce antagonistic selection that constrains adult phenotype, particularly with ecologically distinct developmental phases such as the free-living, feeding larval stage of many frogs (Lissamphibia: Anura). We test the relative influences of developmental and ecological factors on the diversification of adult skull morphology with a detailed analysis of 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 127 publications
1
29
0
Order By: Relevance
“…There is also some evidence of a high rate of lineage accumulation after the re-evolution of metamorphosis in plethodontid salamanders [51]. Contrarily, the loss of an actively feeding larval stage in frogs is associated with higher evolutionary rates in traits associated with feeding specialization [52]. Further work could address the interaction between adaptive radiations and life cycle evolution.…”
Section: Discussionmentioning
confidence: 99%
“…There is also some evidence of a high rate of lineage accumulation after the re-evolution of metamorphosis in plethodontid salamanders [51]. Contrarily, the loss of an actively feeding larval stage in frogs is associated with higher evolutionary rates in traits associated with feeding specialization [52]. Further work could address the interaction between adaptive radiations and life cycle evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Both Nick (1912) and Pritchard and Trebbau (1984) found that the postcranial skeleton of D. coriacea also shows evidence of extensive paedomorphosis, suggesting that the paedomorphic skull may be part of a general skeletal pattern rather than the result of selection directly related to diet and the skull itself. Species develop paedomorphic morphologies in multiple evolutionary contexts, including retention of a juvenile life habit (Kordikova 2002), miniaturisation (Rieppel and Crumly 1997;Bright et al 2016;Esquerré et al 2017), diet (Denoël et al 2004;Esquerré et al 2017;Sherratt et al 2019), and other complex factors which may be unclear (Bright et al 2016;Morris et al 2019;Bardua et al 2021). Unfortunately, the selective pressures for D. coriacea to develop this phenotype are still unkonwn.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial variation in observed in every cranial element (figures 2 and 4 ) and the high disparity is distributed across the crocodyliform skull, particularly in the pterygoid, orbit and quadratojugal, in addition to the snout ( figure 4 ). This pattern is unusual among extant tetrapods, with the other extant archosaur lineage, birds, showing an overwhelming concentration of cranial variation in the anterior rostrum [ 26 , 28 ], while squamates and amphibians show concentrations of high disparity in the elements forming the suspensorium [ 27 , 33 , 40 ]. A more diffuse pattern of cranial disparity and evolutionary rates also characterizes non-avian dinosaurs [ 25 ], which may reflect a greater diversity of trophic niches and food acquisition strategies.…”
Section: Discussionmentioning
confidence: 99%
“…It may also result in antagonistic selection between more terrestrial and more aquatic specializations, limiting the ability to evolve in either direction. That requirement to maintain functionality in both niches may thus constrain and slow their evolution, as has been observed in other semi-aquatic vertebrates such as frogs [ 40 ].…”
Section: Discussionmentioning
confidence: 99%